1998
DOI: 10.1063/1.122261
|View full text |Cite
|
Sign up to set email alerts
|

Transport across conducting ferromagnetic oxide/metal interfaces

Abstract: We have investigated transport properties across interfaces between the conducting ferromagnetic oxides SrRuO3, La0.5Sr0.5CoO3, La0.67Sr0.33MnO3, and the metals Nb, Al, Pd, and Au. The interface resistances range from smaller than 10−8 to 102 Ω cm2, depending on the choice of ferromagnetic oxide and metal. The three conducting metal oxides exhibit distinctly different behavior in their interface resistances with metals, which we believe is due to different processes taking place at the interface. By making the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 11 publications
4
22
1
Order By: Relevance
“…Using the data from Ref. 63 we find that the resistance of the SRO/Au interface can be estimated to be 0.05 lX cm 2 , whereas the resistance of the YBCO/SRO border is about 0.1 lX cm 2 , which is consistent with the data in Ref. 64.…”
Section: Electron Transport In Mesastructuressupporting
confidence: 80%
See 1 more Smart Citation
“…Using the data from Ref. 63 we find that the resistance of the SRO/Au interface can be estimated to be 0.05 lX cm 2 , whereas the resistance of the YBCO/SRO border is about 0.1 lX cm 2 , which is consistent with the data in Ref. 64.…”
Section: Electron Transport In Mesastructuressupporting
confidence: 80%
“…If we assume that the resistance of the LSMO/Au border does not exceed the value of 1 lX cm 2 (Ref. 63) then the resistance of the YBCO/LSMO/Au mesastructure (100 lX cm 2 ) can be explained by the greater resistance of the YBCO/LSMO interface. Using the data from Ref.…”
Section: Electron Transport In Mesastructuresmentioning
confidence: 99%
“…Mieville et al showed that some metal-manganite contacts have tunneling characteristics. 9 Since the transport mechanism in these contacts is supposed to be similar to the transport through grain boundaries, a Cr-LCMO contact ͑S5͒ was studied here.…”
mentioning
confidence: 99%
“…3, we show the much larger MR ratios, ranging between 53 % and 72 %, found by Hueso et al [13] on a series of devices composed of a single MWNT connected to La 0.7 Sr 0.3 MnO 3 (LSMO) electrodes. The very large resistance of the devices, in the 10 MΩ range, comes predominantly from the existence of tunnel barriers between the CNT and the LSMO electrodes (as at most interfaces between LSMO and metals [14]), so that the resistance change between the P and AP configurations, also in the 10 MΩ range, cannot be due to some variation of the considerably smaller electrode or CNT resistances. It can be seen as the MR of a device composed of two tunnel junctions T 1 and T 2 with electrons propagating almost without spin flip between T 1 and T 2 .…”
Section: Review Of Experimental Results On Spin Transport In Metallicmentioning
confidence: 99%